TRADISI SANGKEPAN NASI PADA DADYA DAUH RURUNG KRAMA DESA DUSUN BANTAS DESA PAKRAMAN SUDAJI - Sanjaya Putu (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2019)
Sangkepan is one of the traditions in the village of Pakraman Sudaji which still existed until now. Especially in Bantas hamlet, Pakraman Sudaji village, precisely on Dauh Rurung's chest, there is a unique sangkepan tradition. Krama villages who were present in Sangkepan were treated to food called kemong rice. The kemong rice was made by the village chaplain who got my turn. Sangkepan is carried out once a month precisely every Anggarkasih blessing in a holy place which is a Pura Dadya.Keywords: Tradition, Sangkepan, Village Manners